2009
DOI: 10.1073/pnas.0910803106
|View full text |Cite|
|
Sign up to set email alerts
|

Y chromosome diversity, human expansion, drift, and cultural evolution

Abstract: The relative importance of the roles of adaptation and chance in determining genetic diversity and evolution has received attention in the last 50 years, but our understanding is still incomplete. All statements about the relative effects of evolutionary factors, especially drift, need confirmation by strong demographic observations, some of which are easier to obtain in a species like ours. Earlier quantitative studies on a variety of data have shown that the amount of genetic differentiation in living human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
96
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 32 publications
4
96
1
2
Order By: Relevance
“…Therefore, the opportunity for a stochastic change differs correspondingly and has profound effects on the Y chromosome, particularly when occurring in small populations with low effective deme sizes, such as those that The 'extremely ancient' chromosome that isn't E Elhaik et al have characterized humankind for most of its evolution. 31 In the Mbo samples described by Mendez et al, 2 as having A00 haplotypes, the main contribution to the variation was by genetic drift. Consequently, these haplotypes are derived from a common ancestor who lived only a few centuries ago (Mendez et al 2 ), not 338 000 ya, when a common ancestor of A00 population was reported to live.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, the opportunity for a stochastic change differs correspondingly and has profound effects on the Y chromosome, particularly when occurring in small populations with low effective deme sizes, such as those that The 'extremely ancient' chromosome that isn't E Elhaik et al have characterized humankind for most of its evolution. 31 In the Mbo samples described by Mendez et al, 2 as having A00 haplotypes, the main contribution to the variation was by genetic drift. Consequently, these haplotypes are derived from a common ancestor who lived only a few centuries ago (Mendez et al 2 ), not 338 000 ya, when a common ancestor of A00 population was reported to live.…”
Section: Resultsmentioning
confidence: 95%
“…Within R1-M173, most variation extant in Eurasia is confined to R1a-M420 and R1b-M343. 16 In Europe, R1a is most frequent in the east, and R1b predominates in the west. 17 It has been suggested that this division reflects episodic population expansions during the post-glacial period, including those associated with the establishment of agricultural/ pastoral economies.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Although haploid genealogies capture only a narrow ancestry spectrum of the history of a population's gene pool, they afford a relatively uncomplicated and unique approach to disentangle and investigate complexities created by the superimposition of later gene flow patterns onto preexisting substrates, revealing population formation and affinities as well as insights into gender-related levels of reproductive success. 2,4 Using the conventional Y-chromosome haplogroup nomenclature, the majority of lineages observed in contemporary European populations fall into the following main haplogroups: E, G, I, J, N and R. Typically, 450% of men in Europe are affiliated with haplogroup R. 5,6 Members of haplogroup R are also widespread in Western, 7,8 Central 9 and Southern Asia 10,11 as well as in some parts of the Sahel region of Africa. 12,13 In Europe, essentially all R associates belong to its sub-clade R1 defined by M173.…”
Section: Introductionmentioning
confidence: 99%